Chronic Thromboembolic Pulmonary Hypertension in a Child With Sickle Cell Disease - Spencer, Robert; Valencia Villeda, Gerson; Takeda, Koji; Rosenzweig, Erika B. (Frontiers in Pediatrics, 2020)
Chronic thromboembolic pulmonary hypertension is a potentially curable form of pre-capillary pulmonary hypertension (PH) resulting from incomplete resolution of pulmonary thromboemboli. We describe an 11-year-old boy with homozygous sickle cell disease with an indwelling catheter found to have severe PH on routine screening echocardiography. The diagnosis was confirmed by CT, ventilation-perfusion scintigraphy, and right heart catheterization. The patient was medically managed until undergoing pulmonary thromboendarterectomy with resolution of his PH. This case highlights the need for pediatric providers to be aware of this underdiagnosed form of PH, particularly for patients at high risk.